Deconstructing Retinal Organoids: Single Cell RNA-Seq Reveals the Cellular Components of Human Pluripotent Stem Cell-Derived Retina. (12th January 2019) - Collin, Joseph; Queen, Rachel; Zerti, Darin; Dorgau, Birthe; Hussain, Rafiqul; Coxhead, Jonathan; Cockell, Simon; Lako, Majlinda
Abstract : The rapid improvements in single cell sequencing technologies and analyses afford greater scope for dissecting organoid cultures composed of multiple cell types and create an opportunity to interrogate these models to understand tissue biology, cellular behavior and interactions. To this end, retinal organoids generated from human embryonic stem cells (hESCs) were analyzed by single cell RNA-sequencing (scRNA-Seq) at three time points of differentiation. Combinatorial data from all time points revealed the presence of nine clusters, five of which corresponded to key retinal cell types: retinal pigment epithelium (RPE), retinal ganglion cells (RGCs), cone and rod photoreceptors, and Müller glia. The remaining four clusters expressed genes typical of mitotic cells, extracellular matrix components and those involved in homeostasis. The cell clustering analysis revealed the decreasing presence of mitotic cells and RGCs, formation of a distinct RPE cluster, the emergence of cone and rod photoreceptors from photoreceptor precursors, and an increasing number of Müller glia cells over time. Pseudo-time analysis resembled the order of cell birth during retinal development, with the mitotic cluster commencing the trajectory and the large majority of Müller glia completing the time line. Together, these data demonstrate the feasibility and potential of scRNA-Seq to dissect the inherent complexity of retinal organoids and the orderly birth of key retinal cell types. Stem Cells 2019;37:593–598 : Abstract : Single cell RNA sequencing analysis of human embryonic stem cell-derived retinal organoids allowed identification of retinal cell types over a differentiation time course.